1983
DOI: 10.1073/pnas.80.19.5946
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Robertsonian translocations in man: association of ribosomal genes in the nucleolar fibrillar center in meiotic spermatocytes and oocytes.

Abstract: The spatial relationships of acrocentric chromosomes were studied during prophase I of meiosis in human oocytes and spermatocytes by using cytogenetic techniques, electron microscopy, and in situ hybridization. Ultrastructural investigations revealed an ordered arrangement of nucleolar bivalents at the zygotene and pachytene stages. The end of the bivalent corresponding to the cytological satellite was consistently attached to the nuclear envelope. The fibrillar center of the nucleolus always contained rDNA ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Nonhomologous association of nucleolar chromosomes in human may be accounted for certain non-disjunctions and translocations causing diseases, as in myeloid leukemia (Ohno et al 1961). That model was supported by further studies using the electron microscope to study human meiotic cells (Stahl et al 1983). Moreover, the analysis of Robertsonian translocations in mice indicated that fusion of nucleoli is not the key factor predisposing to centric fusions (Miller et al 1978).…”
mentioning
confidence: 56%
“…Nonhomologous association of nucleolar chromosomes in human may be accounted for certain non-disjunctions and translocations causing diseases, as in myeloid leukemia (Ohno et al 1961). That model was supported by further studies using the electron microscope to study human meiotic cells (Stahl et al 1983). Moreover, the analysis of Robertsonian translocations in mice indicated that fusion of nucleoli is not the key factor predisposing to centric fusions (Miller et al 1978).…”
mentioning
confidence: 56%
“…Mechanisms for centric fusion in man have been proposed by Kurnit (1979), Stahl et al (1983), and Guichaoua et al (1986). These models, despite outward telomeres (or more precisely telomere regions).…”
Section: ) Stochastic Analyses Of Human Chromosomal Aberrationsmentioning
confidence: 99%
“…Blocks of satellite DNA or rDNA sequences are often assumed to constitute preferential breaking points, particularly in the rDNA clusters (Hall and Parker 1995). In humans, the most common structural rearrangements are Robertsonian translocations involving the NOR-bearing chromosomes (Stahl et al 1983;Choo et al 1988). …”
Section: Satellite Dnas Are a Major Component Of Cucumis Centromeresmentioning
confidence: 99%